How does functional connectivity between brain regions differ in individuals with dyscalculia compared to those without? - Zulhelmy, Nurani Fatini; Adi Hanafi, Afifah Hazirah; Yuszaimi, ⁠Nur Aisya Imani; Winoto, Nur Farah Nabilah; Raja Mohamed, Nur Amirah; Che Mohd Nassir, Che Mohd Nasril; Ahmed, Mohamed Ayaaz; Md Tajudin, Huriyyah Hamiemah; Jaffer, Usman (Global Academic Excellence (GAE), 2025)
Dyscalculia, a specific learning difficulty in mathematics, is characterized by impairments in number processing and arithmetic skills. This paper aims to review past and current literature on functional connectivity differences in individuals with dyscalculia compared to typically developing individuals. Our findings show altered connectivity within the intraparietal sulcus (IPS), hippocampus, including the parietal, temporal, and frontal areas. These findings provide valuable insights into the neural mechanisms underlying dyscalculia. Furthermore, this paper also provides insights from the Islamic perspective in addressing dyscalculic issues. Therefore, by having these insights researchers are able to suggest interventions for individuals with dyscalculia.